Barron's finance & investment handbook - Downes, John, 1936-; Goodman, Jordan Elliot (Hauppauge, NY : Barron's, 2014)
Updated to reflect changes in financial regulation and investment strategies caused by the recent global financial crisis, this large reference volume includes an analysis of the full range of current investment opportunities, guidelines for non-experts on what to look for when reading corporate reports and financial news sources, an up-to-date directory of hundreds of publicly traded corporations in the United States and Canada, and a directory listing the names and addresses of brokerage houses, mutual funds families, banks, federal and state regulators, and other major financial institutions. Also includes a financial dictionary with more than 5,000 terms defined. Previous editions of this comprehensive reference book have been called'required reading for students, investors, and writers' by USA Today ,'a fast resource, loaded with information' by Newsday , and'a teeming reservoir of information' by the Oakland Tribune . The brand-new ninth edition is bigger and better than ever, packed with indispensable information for planning and maintaining a healthy investment portfolio.
How to invest your money : 30 key personal investment opportunities -- How to read an annual report -- Understanding the financial news -- Dictionary of finance and investment terms -- Finance and investment ready reference. Sources of information and assistance ; Major financial institutions ; Mutual funds and ETFs ; Historical data ; Publicly traded companies.
Includes bibliographical references and index.
Text in English.
Keywords: Finance; Investments; Finance -- Dictionaries; Investments -- Dictionaries